Menciptakan Ide Kreatif Perspektif Islam - Efendi, Erwan; Endar, Dwi; Sagala, Sohna (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Having creative ideas and applying them in spreading Islamic teachings, his efforts are not only limited to trying to convey messages solely, but he must focus on the continuation of the effect of his communication on the communicant, whether the da'wah messages are sufficient to generate stimulation or encouragement for certain mad'u in accordance with what is expected, or does mad'u remain passive (listen but do not want to carry out) or even reject the messages. A Da'i and Da'iyah must be able to create good creative ideas, namely by always paying attention to the people they face (the congregation), because da'wah must be adapted to the conditions of their mad'u. Therefore preaching to children, youth and parents should ideally be different. This is considering that intelligence and the problems faced by the mad'u. Likewise with the material, because the progress of human thinking is different according to the natural surroundings. This type of research uses a qualitative approach. In this study the authors used qualitative methods with a library research approach. Library research is research that functions to obtain information from books, magazines, documents, historical records or in other words the facilities contained in library. The library approach is research with the activity of finding data from reading books and processing it, which in this case is a creative idea from an Islamic perspective. In the library research process, the library is the main place to get relevant data and information to read and collect, study and record. The results of this study found that in an Islamic perspective creative can be interpreted as an awareness of one's faith, to use all one's abilities, namely as a form of gratitude for Allah's favors in order to make or produce something that is the best and beneficial for life as a form of sincere devotion to Allah's presence.